Institutionalization of stock status report in the management of HIV/AIDS programme: experience from Nigeria - Ademola Joshua Itiola; Chinedu Obi; Abubakar Mohammed; Joseph Raji; Innocent Ibegbunam; Sunday Aguora; Adamu Sambo; Babatunji Odelola (Inishmore Laser Scientific Publishing Ltd, 2019)
Incomplete and poor quality of data generated by routine health information systems limit their use in program planning, implementation and monitoring. Prior to 2012, there was no central structure in place in Nigeria for the collation, analysis and presentation of HIV/AIDS Logistics Management Information System (LMIS) data in a usable format. Following the resolution to unify multiple HIV/AIDS supply chains, the country embarked on an aggressive effort to improve the quantity and quality of LMIS reports. This effort culminated in the periodic generation of Stock Status Report (SSR). The report ensures that LMIS data are collated, analysed and presented in a format that enables stakeholders make informed decisions. In the course of implementation, the country also simplified LMIS tool and adopted a mix of report collection models. The SSR has ensured that Nigeria has a repository of LMIS data that aids program planning, implementation and monitoring. In addition, report generation has stimulated improvement in LMIS data quality for HIV/AIDS and other public health programmes. Our experience suggests that data from routine health information systems (RHIS) is of value in public health programming in resource limited settings. Positive spillover effect is also feasible while simplification of data collection tools can indeed help improve quantity and quality of reports generated through RHIS.